PELANGGARAN LALU LINTAS OLEH ANAK DALAM TEORI KONTROL SOSIAL - Jumriani Nawawi (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2022)
AbstractThis research is focused on how the problem of traffic violations committed by children. This study aims to determine the problems related to the problem that most often occurs in the community in the form of traffic violations by children. Law enforcement against traffic violations by children has been strictly regulated in the legislation, namely Law Number 22 of 2009 concerning Road Traffic and Transportation, but traffic violations by children are still very high. This type of research is a normative juridical research. The research was conducted qualitatively by relying on library research.The results of the study show the forms of traffic violations by children ranging from; don't wear a helmet, don't have a driver's license, run red lights, ride more than two people and drive at high speed. Traffic violations by children are a form of failure of social groups that exist in a child's life, one of which is the family and the individual child's environment.Keywords: Children; Social Control; Traffic violations.